Defining Sexual Harassment in Workplaces: A Policy-Capturing Approach - York, Kenneth M. (Academy of Management Journal, 1989)
In this study, college and university equal employment opportunity officers and university students judged 80 incidents of possible sexual harassment. They were asked if the incidents were cases of sexual harassment and if they would advise that EEOC charges be filed. The subjects were moderately consistent in their judgments and made similar decisions for both questions, weighting three aspects of the incidents most heavily: evidence of coercion, the victim's reaction, and job consequences.